Տրապիզոնի նահանգի հայութեան ցեղասպանութիւնը - Ալվրցեան, Հայկազուն (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В конце Первой мировой войны Османская Империя по факту распалась. Проигравший в войне правительство Талаат-паши подал в отставку. Новое правительство и парламент были вынуждены ответить на ряд вопросов: кто вовлек Турцию в войну, кто организовал депортацию и резню армян и т. д.? Чтобы ответить на эти вопросы в 1919—1921 гг. сформировался Специальный военный трибунал в Константинополе, который организовал судебный процесс над преступниками. В результате более 60 судебных заседаний были вынесены приговоры в отношении ответственных лиц: руководители младотурецкого правительства, центральных органов партии «Единение и Прогресс», региональные руководители партии, губернаторы, другие гражданские и военные должностные лица. Талаат, Энвер, Джемаль и Назим были заочно приговорены к смертной казни, другие обвиняемые получили различные сроки заключения. Этим судебным процессом турецкие власти фактически признают, что произошедшее является геноцидом организованным на государственном уровне. By the end of World War I, the Ottoman Empire had effectively collapsed. Talaat’s defeated government resigned. The new government and parliament had to answer a number of questions: who dragged the country into the war, who organized the deportation and massacres of Armenians, etc.? To answer these questions, the Extraordinary Military Court of Constantinople was established, which organized the trial and sentencing of criminals between 1919 and 1921. More than 60 trials resulted in the sentencing of the perpetrators of the Armenian genocide, central leaders of the “Unity and Progress” Party, the Young Turk government, district party leaders, governors, and other civilian and military officials. Taleat, Enver, Cemal, Nazim were sentenced to death in absentia and many were imprisoned for various terms. The verdict was passed on May 22, 1919 against the officials who carried out the deportations and massacres of the Armenians of Trebizond. Two of the eight perpetrators, Cemal Azmi and Nazim Bey, were sentenced to death in absentia, while the others were sentenced to various terms of imprisonment. With this trial, the Turkish authorities effectively admitted that what had happened was a state-sponsored genocide.
Keywords: Պատմաբանասիրութիւն